The Qur'an and its role in the transformation of Arabian society - Sulaiman, Kabuye Uthman (2013)
The Qur’an is the basis of Islam and an intrinsic part of a Muslim life. It is a gateway to a new world, the strong rope that connects Muslims to their Lord, Allah, the Straight Path (al-Sirat al-Mustaqim) leading them to everlasting bliss and the backbone of their success in both existences, i.e. al-Dunya and al-Akhirah (here and hereafter). Since its revelation great transformations have taken place including the transformation of Arabia from jahiliyyah (ignorance) to enlightenment, from polytheism (the worship of multitude of deities besides Allah which is termed as shirk or kufr) to monotheism (tawhid or the worship of one God, Allah), from unjust to a well-organized society (socially, economically and politically), from a fragmented into a unified community and from Godless into God-conscious. The aim of this paper is to discuss the role of the Qur’an in the transformation of the Arabian society. It contends that no book has transformed societies the way the Qur’an has.